Intensive Technology of Mosh Cultivation in Khorazm Region (Texas Journal of Agriculture and Biological Sciences, 2023)
This article describes the technology of cultivation, methods and also increasing the yield of mung bean grain as a repeat crop after winter wheat in conditions of irrigated meadow alluvial soils.